XR Collaboration Architecture based on Decentralized Web - Huh Seungyeon; Shapna Muralidharan; Ko, Heedong; Byounghyun Yoo (PROCEEDINGS WEB3D 2019: THE 24TH INTERNATIONAL ACM CONFERENCE ON 3D WEB TECHNOLOGY, 2019)
The web has been an extremely effective collaboration platform, enabling services like Wikipedia article co-authoring, blogging, social messaging, video conferencing, and many others. However, the collaboration should ideally occur Peer to Peer (P2P) among the participants instead of going through a centralized server as in the current centralized web, which acts as a mediator as well as a repository of data, especially for face-to-face collaboration in 3D XR context. Most notable XR applications like MMORPG have been developed in a dedicated application platform with their own centralized game servers. Nowadays, the decentralized web is being promoted as the next web architecture in numerous fronts such as blockchain in cryptocurrency, reviving P2P storage, and networking technologies as the next web, Web 3.0. It would be beneficial if we could make an XR collaboration framework based on the recent developments of the decentralized web. This paper explores one possible amalgamation of the decentralized web technology stack toward a webized XR collaboration framework.